Neuroprotective Effects of Secondary metabolites as a inhibitor of Acetylcholinestrase (Ache) for treatment of Alzheimer’s Disease : An in silico Approach - Mohd Aziz; Firdaus Jahan; Kavita Sharma; Priya Gouri; Anil Sharma (The Bioscan, 2024)
Neurodegenerative disorders (NDD) constitute a series of pathological conditions which originating from slow progressive and irreversible dysfunction and can lead to loss of neurons and synapses in selected areas of the brain which determine clinical presentation and course. Common neurodegenerative disorders are Alzheimer's disease, Huntington's disease, amyotrophic lateral sclerosis, Parkinson's disease , frontotemporal dementia and the spinocerebellar ataxias. The study was designed to find the Effects of secondary metabolites as a potent inhibitor of Acetylcholinestrase (Ache) by in silico approach with help of Lipinski And ADME analysis for treatment of Alzheimer’s Disease. Out of 100 compound , find 5 compound Alpha-lapachone, Harmaline ,Harmine, Daidzein, Isopimpinellin are actively inhibit the Activity of Ache out of five, “Daidzein” is most effective inhibitor of Ache according to Docked Score compared to Donepezil and Galantamine Which are already present for treatment of Alzheimer’s Disease.